Erythrocytes as Potential Link between Diabetes and Alzheimer’s Disease - Carelli-Alinovi, Cristiana; Misiti, Francesco (Frontiers in Aging Neuroscience, 2017)
Many studies support the existence of an association between type 2 diabetes (T2DM) and Alzheimer’s disease (AD). In AD, in addition to brain, a number of peripheral tissues and cells are affected, including red blood cell (RBC) and because there are currently no reliable diagnostic biomarkers of AD in the blood, a gradually increasing attention has been given to the study of RBC’s alterations. Recently it has been evidenced in diabetes, RBC alterations superimposable to the ones occurring in AD RBC. Furthermore, growing evidence suggests that oxidative stress plays a pivotal role in the development of RBC’s alterations and vice versa. Once again this represents a further evidence of a shared pathway between AD and T2DM. The present review summarizes the two disorders, highlighting the role of RBC in the postulated common biochemical links, and suggests RBC as a possible target for clinical trials.